EDUTOURISM LANDSCAPE PLANNING IN SUKAMULYA VILLAGE, BOGOR DISTRICT - Indah Ulfia Utami; Priambudi Trie Putra; Moh. Sanjiva Refi Hasibuan (Universitas Trisakti, 2023)
Sukamulya village is located in Sukamakmur district, Bogor regency. This village is also included in the plan to develop and repair the Puncak Dua line carried out by the Bogor district government. Sukamulya village has a rural landscape with main activities such as agriculture, plantations, and agroforestry. Coffee is one of the primary commodities that is quite potential since the development of coffee plantations in this area. In addition, Sukamulya village's landscape consists of hills with good views and a relatively large river, namely the Cipamingkis river. The site's location is in an area with fertile soil conditions but has a potential risk of moderate-category landslides. This area also needs better access and needs facilities to support tourist activities. This also makes this area lag behind compared to the area traversed by the Puncak Utama route. This article discussed the landscape planning process of Sukamulya Village, which has the potential to be developed as an educational tourism destination in order to compete with other tourist attractions in the Puncak area. The method used in this research is descriptive and scoring with SWOT Analysis. The stages of the landscape planning process are carried out, starting with inventory activities, data analysis, synthesis, and producing a block plan. The analysis results show that efforts are needed to increase the potential of local resources, such as conducting environmental conservation. Landscape planning of Sukamulya Village as educational tourism produces three zoning divisions: the intensive zone, semi-intensive zone, and extensive zone. Further studies are needed on the variety of forms of tourism activities that have educational value in Sukamulya village in order to be able to compete with other tourist attractions in the region and be sustainable.